POTENSI DESA BELALANG SEBAGAI DESA WISATA UNTUK MENUNJANG KEPARIWISATAAN KABUPATEN TABANAN - I Made Bayu Wisnawa; Gusti Ayu Mahanavami (Forum Manajemen, 2014)
Desa Belalang is a rural village in Tabanan, Bali has a high valuetourism potential to be developed to improve the wellfare of society. This study aimsto (i) determine the potential locust village so it can be developed as tourist villagesand (ii) determine the constraints encountered in developing Desa Belalang as atourist village.By using qualitative methods and techniques SWOT, in depth interview on the headof the village, tourists, businessmen and villagers then the results of this studyare; (i) Desa Belalang has tourim potential such as: attractions, access, ancillaryand community involvement, (ii) Constraints faced are: Desa Belalang yet specialorganization that manages the tourism, and the population is not all houses intraditional Balinese house concept. The efforts which should be implemented bydeveloping the tourism human resources, partnerships, promotion, festival, communitydevelopment organizations and cooperation with higher education institutions.